WORKSHOP PEMBUATAN MIKROORGANISME LOKAL BERBASIS LIMBAH POHON PISANG DI DESA GUNUNG AGUNG - Akmal Hammami; Nabila Cahyani; Adzra Lutfi Afifah; Usman Jordi; Upi Laila Harnum; Hafiza Eka Ramadhini; Adinda Shafa Khairunnisa; Tulus Sahgohan Sihite; Yoan Azari; Rifaldi Setyo Wibowo; Tri Anjelly Silalahi; Resi Rasyta Dewi; Sophiara Tamami Batubara; Muhammad Ridwan Hafidz; Samuel Hasudungan Hutagalung; Teny Sylvia (UPT. PKM UB, 2024)
Gunung Agung is a village in the Terusan Nunyai District, Central Lampung Regency, Lampung Province, Indonesia, with social diversity and cultural richness produced by its bustling community. Gunung Agung Village has geographical conditions that support the agricultural sector. The farmland covering a large village area is planted with various crops, especially cassava and sugarcane. The topography and fertile soil create good opportunities for productive agriculture. Cassava and sugarcane are local food sources and have significant economic potential for village communities. One effort to increase agricultural yields can be made by improving cultivation systems, such as implementing sustainable organic farming methods using liquid organic fertilizer. Fertilizer from organic and inorganic materials is used to increase soil fertility. Through community service activities, additional knowledge regarding liquid organic fertilizers, especially those produced from local microorganisms (MOL) banana weevils, is conveyed through various methods such as socialization and training in making banana weevil MOL. Thus, the people of Gunung Agung village can develop their understanding of increasing crop yields by utilizing liquid organic fertilizer based on banana hump MOL which can be obtained easily.